Discovering associations in very large databases by approximating - Zhang, Schichao; Zhang, Chengqi (Acta Cybernetica, 2003)
Mining association rules has posed great challenge to the research community. Despite efforts in designing fast and efficient mining algorithms, it remains a time consuming process for very large databases. In this paper, we adopt a slightly different approach to this problem, which can mine approximate association rules quickly. By considering the database as a set of records that are randomly appended, we can apply the central limit theorem to estimate the size of a random subset of the database, and discover both positive and negative association rules by generating all possible useful itemsets from the random subset. However, because of approximation errors, it is possible for some valid rules to be missed, while other invalid rules may be generated. To deal with this problem, we adopt a two phase approach. First, we discover all promising approximate rules from a random sample of the database. Second, these approximate results are used as heuristic information in an efficient algorithm that requires only one-pass of the database to validate rules that have support and confidence close to the desired support and confidence values. We evaluated the proposed technique, and our experimental results demonstrate that the approach is efficient and promising.